2022
DOI: 10.1139/cjas-2021-0124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrogenated fat-embedded calcium gluconate on lactation performance in dairy cows

Abstract: Hydrogenated fat-embedded calcium gluconate (HFCG), a prebiotic mixture designed to target the hindgut, has improved milk and component yields when supplemented in mid-lactation cows, likely due to improved hindgut health. The objective of this study was to evaluate production responses to HFCG when fed to lactating dairy cattle over a full lactation. Seventy-four Holstein cows (21 primiparous, 53 multiparous) were used in a randomized complete block design comparing supplementation with either HFCG (approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…Given what is known about the importance of hindgut health in non-ruminant species, specifically targeting the ruminant hindgut with prophylactic interventions is an opportunity that merits exploration. We have previously observed increases in yields of milk fat (Seymour et al, 2020(Seymour et al, , 2021 and/or protein (Sanz-Fernandez et al, 2022;Seymour et al, 2022) when supplementing lactating dairy cattle with approximately 16 g/d hydrogenated fat-embedded calcium gluconate (HFCG), a prebiotic compound specifically targeting the increased production of acetate and/or butyrate in the hindgut (Asano et al, 1994;Tsukahara et al, 2002Tsukahara et al, , 2006. However, the underlying mechanism(s) of these responses remain unclear at present.…”
mentioning
confidence: 99%
“…Given what is known about the importance of hindgut health in non-ruminant species, specifically targeting the ruminant hindgut with prophylactic interventions is an opportunity that merits exploration. We have previously observed increases in yields of milk fat (Seymour et al, 2020(Seymour et al, , 2021 and/or protein (Sanz-Fernandez et al, 2022;Seymour et al, 2022) when supplementing lactating dairy cattle with approximately 16 g/d hydrogenated fat-embedded calcium gluconate (HFCG), a prebiotic compound specifically targeting the increased production of acetate and/or butyrate in the hindgut (Asano et al, 1994;Tsukahara et al, 2002Tsukahara et al, , 2006. However, the underlying mechanism(s) of these responses remain unclear at present.…”
mentioning
confidence: 99%
“…Our group has previously observed increases in yields of milk fat ( Seymour et al, 2021 , 2023 ) and/or protein ( Sanz-Fernandez et al, 2022 ; Seymour et al, 2022 ) to varying degrees in response to supplementing HFCG in lactating dairy cattle. In particular, Seymour et al (2022) employed treatments synonymous with the GG and CC sequences used in the present study; while a time-dependant response to supplementation was also observed in multiparous cattle, increases in milk fat and protein yield occurred over the first 8 wks of lactation.…”
Section: Discussionmentioning
confidence: 87%
“…Our group has previously observed increases in yields of milk fat ( Seymour et al, 2021 , 2023 ) and/or protein ( Sanz-Fernandez et al, 2022 ; Seymour et al, 2022 ) to varying degrees in response to supplementing HFCG in lactating dairy cattle. In particular, Seymour et al (2022) employed treatments synonymous with the GG and CC sequences used in the present study; while a time-dependant response to supplementation was also observed in multiparous cattle, increases in milk fat and protein yield occurred over the first 8 wks of lactation. We have confirmed that while no differences between the CC and GG sequences for any outcome over the first 8 wks of lactation were found ( P ≥ 0.274), the magnitude of the responses in yields of milk and milk components observed, while observed later in lactation, were consistent with those reported by Seymour et al (2022 ; approx.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations